An Examination of Herding Behavior in the Brazilian Equity Market - Patrícia Fernanda Correia Lima Signorelli; Eduardo Camilo-da-Silva; Claudio Henrique da Silveira Barbedo (BBR: Brazilian Business Review)
The aim of the present study is to investigate herding behavior in the Brazilian stock market. This bias is quite common in times of market downturns and can cause investors to suffer large losses. It is very difficult to effectively identify its real occurrence. Through the method of Chang et al. (2000), it is possible to show that the occurrence of herd behavior is associated with the following phenomena: high trading volume; high volatility, market downturn; and misbalancing of orders. The main contribution of the paper is to identify that herding behavior reacts asymmetrically to the sign of past shocks. The results suggest that an intense selling movement can generate uncertainty in agents, causing them to imitate others in imminent loss periods.